Alpha Mangostin and Xanthone from Mangosteen (Garcinia mangostana L.) Role on Insulin Tolerance and PPAR-γ in Preclinical Model Diabetes Mellitus - Welly Ratwita; Elin Yulinah Sukandar; NengFisheriKurniati; I Ketut Adnyana (Journal of Pharmacy and Nutrition Sciences, 2018)
Objective: This research elaborated role of alpha mangostin and xanthone on insulin resistance and peroxisome proliferator–activated receptor (PPAR)-γ by measuring blood glucose level and PPAR- γ expression on adipocyte cell culture. Methods: Insulin tolerance test were conducted using male wistar rat divided into 9 groups, which were normal, control (D-Glucose induced only), glibenclamide, various doses of a-mangostin and xanthone (5, 10, 20 mg/kgbw). All group induced by D-glucose 3 g/kg orally 30 minutes later. Blood glucose levels changes were observed at 90th and 150th minute. While other study observed PPAR-γ expression on adipocyte cell culture that treated with a-mangostin/xanthone/pioglitazone in various concentration. Results: KITT in all treatment groups were significantly different (p<0.05) when compared to the positive control group, except xanthone 5 mg/kgbw. This suggests that a-mangostin 5, 10 and 20 mg/kgbw, xanthone 10 and 20 mg/kgbw, as well as metformin, have the effect of lowering insulin resistance in white rats given a 10-day fatty emulsion. Almost similar with thiazolinedione, alpha mangostin and xanthone increase PPAR-g expression in adipocyte when the concentration bigger. But xanthone effect not as good as α-mangostin or thiazolinedione effect. Conclusion: Alpha mangostin and xanthone are two substances that showed potential effect to improve insulin tolerance by increasing PPAR-g in adipocyte.